Data on the effect of wood-based panel-emitted volatile organic compounds on miceMendeley Data - Inho Hwang; Kangmin Kim; Sun-Hwa Ryu; Changhwan Ahn; Xiang-Shun Cui; Eui-Bae Jeung (Data in Brief)
Wood based panels are widely used in construction and furniture due to their cost effectiveness, sustainability, and processability. However, adhesives and additives used in these engineered materials may release volatile organic compounds (VOCs), including formaldehyde and BTEX compounds, affecting indoor air quality. This study presents a dataset examining VOC emissions from three commonly used panels: pine wood board (PWB), low pressure melamine particleboard (LPM), and particleboard (PB), and their potential health impacts in mice. To reflect a real-life early-phase exposure scenario, the panels were not pre-conditioned and were installed on three sides of a 50 × 50 × 50 cm acrylic chamber with passive air exchange only. Air samples were collected nine times over 14 days using automatic thermal desorption gas chromatography/mass spectrometry (ATD GC MS). VOCs were categorized as total VOCs (TVOC), natural VOCs (NVOC), five hazardous VOCs (BTEX plus styrene; 5VOC), and formaldehyde. Male BALB/c mice (n = 4 per group) were continuously exposed to each chamber for 14 days. Body weight was monitored on days 7 and 14, and 21 hematological and serum biochemical parameters were analyzed after exposure. Organs including the liver, kidney, lung, heart, and spleen were weighed and histologically examined. The dataset includes time resolved emission profiles for each panel type, longitudinal body weight measurements, blood and serum biochemical markers, and histological images. VOC emissions varied by material, with detectable formaldehyde in LPM and PB, and predominantly NVOC in PWB. No abnormal behaviors were observed during exposure. Statistically significant differences were noted in some blood parameters and organ weights between control and exposed groups, although all values remained within the normal physiological range. Histopathological analysis likewise revealed no specific abnormalities. This dataset supports future studies on VOC exposure response modeling, regulatory benchmarking, or risk mitigation strategies and contributes to understanding acute biological responses to real world wood panel emissions.